Quantitative Analysis of Working at Home During The Covid-19 Pandemic - Yohanes Susanto; Irwan Pancasila; R.A. Zubaidah Zubaidah; Fitria Marisya (Ilomata International Journal of Management, 2022)
Although many studies have shown that Working from home (WFH) has a positive impact on the organization, the consequent covid-19 outbreak shows an important disadvantage associated with increasing levels of WFH. This research intends to look into the possibilities for improving employee performance from working at home, we examine how increasing WFH affects the work environment, workload, organizational culture. Our study is based on data from an online survey of 68 employees at the Land Agency of Musirawas Regency, South Sumatra, Indonesia. The results show that the predominant level of WFH during civid-19 isolation causes more workload, and less organizational culture. In addition, The study's findings demonstrate the strong interconnectedness of tasks between the work environment, workload and organizational culture to realize good employee performance. In such a way that Our research adds to the literature on the potential detrimental organizational impacts brought on by the rising requirement for WFH. Organizations should design remedies to better incorporate WFH personnel into daily operations to lessen their sense of social isolation and increase organizational identification.